Temporary Shutdown of ERK1/2 Phosphorylation Is Associated With Activation of Adaptive Immune Cell Responses and Disease Progression During Leishmania amazonensis Infection in BALB/c Mice - Oliveira, Leandro G.; Souza-Testasicca, Míriam C.; Ricotta, Tiago Nery Queiroga; Vago, Juliana P.; dos Santos, Liliane M.; Crepaldi, Frederico; Lima, Kátia M.; Queiroz-Junior, Celso; Sousa, Lirlândia P.; Fernandes, Ana Paula (Frontiers in Immunology, 2022)
Leishmania spp. infection outcomes are dependent on both host and parasite factors. Manipulation of host signaling pathways involved in the generation of immune responses is thought to be one of the most common mechanisms used by parasites for persistence within the host. However, given the diversity of pathologies caused by different Leishmania spp., it is plausible that significant differences may exist in the mechanisms of host cell manipulation and they should be considered when developing new vaccine or treatment strategies. Herein, we show that in in BALB/c mice, while in the resistant model of L. braziliensis-infection activation of ERK1/2 coincides with the peak of inflammatory responses and resolution of tissue parasitism, an early, silent phase of infection occurs in the susceptibility model of L. amazonensis-infection, detected solely by quantification of parasite loads. At this early stage, only basal levels of P-ERK1/2 are observed. Later, after a brief shutdown of ERK1/2 phosphorylation, disease progression is observed and is associated with increased inflammation, lesion size and tissue parasitism. Moreover, the short-term down-regulation of ERK1/2 activation affected significantly downstream inflammatory pathways and adaptive T cell responses. Pharmacological treatment with U0126, a MEK/ERK inhibitor, confirmed this phenomenon, since bigger lesions and higher parasite loads were seen in infected mice treated with U0126. To investigate how kinetics of ERK1/2 activation could affect the disease progression, U0126 was administered to L. amazonensis-infected animals earlier than the P-ERK 1/2 switch off time-point. This intervention resulted in anticipation of the same effects on inflammatory responses and susceptibility phenotype seen in the natural course of infection. Additionally, in vitro inhibition of ERK1/2 affected the phagocytosis of L. amazonensis by BMDMs. Collectively, our findings reveal distinct patterns of activation of inflammatory responses by L. braziliensis and L. amazonensis infections the same model . More importantly a pivotal role for a brief shut-down of the ERK1/2 activation on disease progression at late stages of L. amazonensis infection. Since activation of inflammatory responses is crucial for the control of infectious processes, these findings may be important for the search of new and specific strategies of vaccines and treatment for tegumentary leishmaniasis.